Changes in corallite sizes of scleractinian corals across major hyperthermal events - Dimitrijevic, Danijela; Raja Schoob, Nussaibah Begum; Kießling, Wolfgang (Progressive Palaeontology 2021 - Online, 2021)
Global warming today is taking its toll on coral reefs globally, particularly affecting scleractinian corals which rely on their symbionts for nutrition. In the past, hyperthermal events have probably triggered evolutionary losses and gains of symbiosis in corals. Accordingly, we expect photosymbiotic corals to be more strongly affected than non-symbiotic corals. Corallite sizes have been used as a proxy for the efficacy of photosymbiosis with smaller corallite sizes associated with higher photosymbiotic autotrophy in colonial corals. Using a new database on corallite sizes of fossil corals collected from existing literature and data on modern corals from the Coral Trait Database combined with occurrences from the Paleobiology Database, we test how the dependency on photosynthetic diet in corals may have increased their extinction risk. We expect corals to be selected against small corallite sizes during hyperthermal events. Based on a survey of 353 fossil and recent coral genera we establish trends in corallite sizes across the Triassic–Jurassic, Pliensbachian–Toarcian, Barremian–Aptian, Cenomanian–Turonian, and Paleocene–Eocene. We find a significant increase in corallite diameter of all corals at three of these events. Colonial corals had 0.8 times larger corallites in the Aptian than in the Barremian suggesting stronger heterotrophy at this hyperthermal event. However, generalized linear modelling suggests that the extinction of scleractinian corals seems to be non-selective with regards to their corallite sizes. This indicates that processes other than warming, such as increased sediment input could be the cause of this change.<br